Modeling of multi-wavelength brillouin fiber laser based on analytical solutions in a linear cavity - Al-Mashhadani T.F.; Jamaludin M.Z.; Al-Mansoori M.H.; Abdullah F.; Abass A.K. (2023)
In this article, an accurate model of multi-wavelength Brillouin fiber laser is developed by analytically solving cascade-stimulated Brillouin scattering equations in a linear cavity. The dependence of Stokes signal power on the incident pump power and the successive reflected transmitted powers is calculated. Furthermore, an analytical approach that can be used to predict the generated Stokes signals power is derived. Finally, this derived model is checked with experimental results that show significant agreement with the analytical solution of the model. 2012 Taylor & Francis Group, LLC.